1974
DOI: 10.1017/s0003356100022583
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between dietary lipids and fibre in the sheep 2. Digestibility studies

Abstract: Digestibility studies were carried out to establish the inter-relationship between crude fibre and total lipid digestibility in the presence of added calcium or non-ionic detergents. Three levels of calcium, corresponding to daily intakes of 2-3, 4-8 and 22-9 g per sheep, were used in a predominantly ground barley diet (65 to 73 %) to which was added 8 % beef tallow or maize oil. Two non-ionic detergents were used at 0-1 % of the diet: nonyl phenol ethylene oxide and fatty alcohol combined with 3 molecules of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
11

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 22 publications
6
55
1
11
Order By: Relevance
“…Moreover, diets with a higher fat content usually results in lower digestibility as a result of modification of the ruminal microbial population, inhibition of microbial activity, and reduced cation availability (Devendra and Lewis 1974). Diets containing CA were higher in fat content than those with SB (Table 1) and extrusion increased DM disappearance of CA but not of SB (Table 2); this could suggest that more fat was digested in the rumen with EXCA than with other treatments, which could result in decreased fiber digestion in the rumen when feeding EXCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, diets with a higher fat content usually results in lower digestibility as a result of modification of the ruminal microbial population, inhibition of microbial activity, and reduced cation availability (Devendra and Lewis 1974). Diets containing CA were higher in fat content than those with SB (Table 1) and extrusion increased DM disappearance of CA but not of SB (Table 2); this could suggest that more fat was digested in the rumen with EXCA than with other treatments, which could result in decreased fiber digestion in the rumen when feeding EXCA.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, extrusion has the potential of reducing CP degradability as shown in lupin seeds (Cros et al 1992), which could improve the nutritive value of seed as a source of undegraded protein. Khorasani et al (1992) suggested that reducing degradability of the protein-rich matrix surrounding the fat droplets of CA could overcome the negative effects of supplemental fat on ruminal digestion (Devendra and Lewis 1974). The objectives of this experiment were to determine the effect of extrusion of full fat seeds on performance of lambs fed a high-forage diet and to compare growth and carcass quality of growing lambs fed either CA or SB.…”
Section: Mots Clésmentioning
confidence: 99%
“…Adverse effects of supplemental fat (more than 4%) on DMI of lactating dairy cattle are well documented (Allen 2000). Mechanisms by which high level of supplemental fat adversely affect DMI include interference with acceptability of diet, reduced gut motility, decreased fermentation and degradation of fiber, and alteration of hormonal status (Devendra and Lewis 1974;Palmquist and Jenkins 1980;Allen 2000).…”
Section: Nutrient Densitymentioning
confidence: 99%
“…However, dietary fat supplements are known to cause negative modification to fermentation and nutrient digestion in the rumen. Reductions have been demonstrated in fibre and organic matter digestion, methanogenesis, ammonia concentrations and acetate:propionate value (Devendra and Lewis, 1974;Palmquist and Jenkins, 1980). Therefore, various methods such as formaldehyde-treated emulsions of fat in proteins (Scott et al, 1971), calcium soaps (Jenkins and Palmquist, 1982), heat treatment (Tice et al, 1994), fatty acyl amides (Fotouhi and Jenkins, 1992), the crystalline hydrogenated fat (Elliott et al, 1994) and feeding whole oilseeds (Scollan et al, 2001) for protecting fat sources from rumen metabolism, which offers the possibility that fat sources fed in such a form may interfere less with rumen metabolism.…”
Section: Introductionmentioning
confidence: 99%